2005
DOI: 10.1093/occmed/kqi110
|View full text |Cite
|
Sign up to set email alerts
|

Violence toward mental health staff and safety in the work environment

Abstract: Threats and assaults on mental health staff have a substantial prevalence and are increasing in our psychiatric population. Practical recommendations derived from our study but in need of further research for confirmation are: (1) multidisciplinary personal safety training to enhance team-building, improve communication and help prevent violent events and (2) establishment of post-event protocols to assist staff-victims and administrators navigate through complex issues occurring after violent events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
69
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 9 publications
10
69
0
5
Order By: Relevance
“…Using different questionnaires, research conducted in England 8) , Hong Kong 9) , and China 10) found that PV varied from 5.3% to 21% and VA from 43% to 73%. Studies conducted in emergency departments and psychiatric settings in the US 11,12) , Kuwait 13) , and Taiwan 14) found even higher prevalence rates. However, it is difficult to compare these studies directly because of the different definitions of workplace violence used and the different durations of recall used in the studies.…”
Section: Field Studymentioning
confidence: 96%
“…Using different questionnaires, research conducted in England 8) , Hong Kong 9) , and China 10) found that PV varied from 5.3% to 21% and VA from 43% to 73%. Studies conducted in emergency departments and psychiatric settings in the US 11,12) , Kuwait 13) , and Taiwan 14) found even higher prevalence rates. However, it is difficult to compare these studies directly because of the different definitions of workplace violence used and the different durations of recall used in the studies.…”
Section: Field Studymentioning
confidence: 96%
“…Moreover, relative to other private sector industries, the mental health sector has a higher incidence of workplace violence (Privitera, Weisman, Cerulli, Tu, & Groman, 2005). Because many of these unique challenges and stressors are not easily ameliorated, job resources such as supervisor autonomy support, selfefficacy, and staff cohesion may play an even more important role in the mental health field compared to other sectors.…”
mentioning
confidence: 99%
“…Patients do not recognize the risks of medical care, resulting in an increasing number of lawsuits 10) . Nurses and patient care assistants who have close patient contact are often reported to be exposed to violence 1,2,11,12) . There are a few studies on violence perpetrated on physicians that focus on emergency doctors and psychiatrists in other countries however, similar studies have not been conducted in Japan 9,[13][14][15] .…”
mentioning
confidence: 99%